PENGARUH MOTIVASIi, DISIPLIN KERJA DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA KANTOR BPN KABUPATEN BOGOR - Wicaksono, Bambang Wahyudi; Albarto, Yohanes; Karjono, Albertus (Gapenas Publisher, 2024)
Success in achieving a company's goals is greatly influenced by employee performance. Every company will always improve employee performance in the hope that the company's goals are maximally achieved. This study aims to find out whether motivation, work discipline and communication simultaneously and partially have a significant effect on employee performance at the BPN office in Bogor Regency. The research method used is associative research. The population in this study is 75 ASN staff who have worked for at least 2 years, in addition to the leaders at the BPN office of Bogor Regency. Sampling uses a nonprobability sampling technique, namely saturated sampling with the sample taken are 75 ASN staff who have worked for at least 2 years, in addition to the leaders at the BPN office of Bogor Regency. The data analysis techniques used include questionnaire validity test, questionnaire reliability test, respondent profile analysis, descriptive analysis and multiple linear regression, determination coefficient, F test and t test. The results of the t-test showed that motivation, work discipline and communication partially had a significant effect on employee performance at the BPN office in Bogor Regency